2012
DOI: 10.1007/s10266-012-0074-1
|View full text |Cite
|
Sign up to set email alerts
|

Wear and mechanical properties of composite resins consisting of different filler particles

Abstract: To investigate the effects of different fillers and their contents on the wear of composite resins, four composites (CS: non-porous spherical silica, AS: porous spherical silica, AZ: porous spherical zirconium silicate, and IS: non-porous irregular-shaped silica) were experimentally prepared using different fillers (CS, AZ, AS and IS). Simulated occlusal wear and toothbrush wear were evaluated for these composites and their worn surfaces were observed. The mechanical properties (flexural strength, elastic modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Another aspect that might have affected the surface property of the evaluated composites is the shape of their filler particles, since Z100, Supreme Ultra, and Estelite ∑ Quick have spherical/rhomboid fillers, in contrast to the other tested materials, which present irregularly shaped fillers. Tamura, Kakuta, and Ogura () have suggested that irregularly shaped fillers might receive more frictional forces during abrasion than spherical particles, as they have corners and sharp edges that can be easily caught by abrasives and/or toothbrush bristles, which could facilitate their removal and enhance toothbrushing‐induced wear. Besides, EDX analysis (Figure ) showed the composites with smaller fillers tested in this study have an inorganic portion composed by silica and zirconia particles.…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect that might have affected the surface property of the evaluated composites is the shape of their filler particles, since Z100, Supreme Ultra, and Estelite ∑ Quick have spherical/rhomboid fillers, in contrast to the other tested materials, which present irregularly shaped fillers. Tamura, Kakuta, and Ogura () have suggested that irregularly shaped fillers might receive more frictional forces during abrasion than spherical particles, as they have corners and sharp edges that can be easily caught by abrasives and/or toothbrush bristles, which could facilitate their removal and enhance toothbrushing‐induced wear. Besides, EDX analysis (Figure ) showed the composites with smaller fillers tested in this study have an inorganic portion composed by silica and zirconia particles.…”
Section: Discussionmentioning
confidence: 99%
“…The adhesion between filler and polymerized resin matrix could also be related to the wear resistance of flowable resin composites. Tamura, et al 19 (2013) reported that the filler loading is directly related to the occlusal wear of experimental resin composites containing four types of filler particles, including non-porous spherical silica, porous spherical silica, porous spherical zirconium silicate, and irregularshaped silica. However, the mechanical properties tested (flexural strength, elastic modulus, and Vickers hardness) showed no correlation with the occlusal wear.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the increased in filler loading and decreased in filler size improves wear resistance as well as aesthetics of dental composite [55][56][57][58]. In a recent work, the effects of different shapes, surface textures, structures and content of nanoalumina filler particles on the wear and mechanical properties on simulated occlusal wear and toothbrush wear were investigated [59]. It was concluded that the incorporation of nanofiller increased both the hardness and wear resistance of the dental composites and they also produced better polished surface than micro-filler.…”
Section: Influence Of Filler Constituents On the Performance Of Dentamentioning
confidence: 99%